2018
DOI: 10.1186/s13019-018-0726-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pericardial approach and myocardial protection onto postoperative right ventricle function reduction

Abstract: BackgroundThe reduction of RV function after cardiac surgery is a well-known phenomenon. It could persist up-to one year after the operation and often leads to an incomplete recovery at follow-up echocardiographic control. The aim of the present study is to analyze the impact of different modalities of pericardial incision (lateral versus anterior) and of myocardial protection protocols (Buckberg versus Custodiol) onto postoperative RV dynamic by relating two- and three-dimensional echocardiographic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…From patient collectives undergoing surgical repair of MR, it is known that two-dimensional (2D) indexes of RV systolic performance decrease during and immediately after cardiac surgery [5]. Moreover, recovery to basal values is often incomplete and an echocardiographic dysfunction can persist even at one year after surgery [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From patient collectives undergoing surgical repair of MR, it is known that two-dimensional (2D) indexes of RV systolic performance decrease during and immediately after cardiac surgery [5]. Moreover, recovery to basal values is often incomplete and an echocardiographic dysfunction can persist even at one year after surgery [5].…”
Section: Introductionmentioning
confidence: 99%
“…From patient collectives undergoing surgical repair of MR, it is known that two-dimensional (2D) indexes of RV systolic performance decrease during and immediately after cardiac surgery [5]. Moreover, recovery to basal values is often incomplete and an echocardiographic dysfunction can persist even at one year after surgery [5]. Depression of RV function is also reported for other settings of cardiac surgery like coronary artery bypass grafting [6], and worsening of RV function and the magnitude of deterioration have important prognostic implications for interventions such as transcatheter aortic valve replacement (TAVR) [7].…”
Section: Introductionmentioning
confidence: 99%
“…36 Reductions in right heart function have been well described after cardiac surgery, and are thought to be secondary to inadequate myocardial protection, use of cardiopulmonary bypass, postoperative adhesions to surrounding structures such as the sternum, and pericardial disruption. Reductions in echocardiographic measures of right heart function including right ventricular tissue Doppler velocities and transannular plane systolic excursion (TAPSE) and have been described in patients undergoing traditional procedures such as coronary artery bypass grafting (CABG), aortic valve replacement (AVR), and mitral valve repair (MVR) via sternotomy, 15,16,37,37,38 with an acute decline occurring just after pericardial incision. 15,16 Interestingly, these findings are not seen in patients undergoing non-sternotomy approaches, such as robotic CABG and ministernotomy-AVR, and thoracotomy MVR in which the anterior pericardial restraint over the right heart is preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported a change of RV geometry or reduction of RV systolic function after pericardial incision without suture [ 7 , 15 17 ], which was similar with our study. Interestingly, the study by Zanobini M, et al [ 18 ] also reported the presence of decreased RV systolic function after pericardial incision even with reclosing the pericardium with a continuous suture in different surgical approach and cardioplegia type. The possible mechanisms of decreased RV function after cardiac surgery may be related to the cardiopulmonary bypass use, pericardial adhesions, modality of cardioplegia delivery and pericardial incision, and so on [ 18 ], and its clear-cut mechanisms were warranted to be further addressed in the future study.…”
Section: Discussionmentioning
confidence: 99%